2000
DOI: 10.1074/jbc.m910207199
|View full text |Cite
|
Sign up to set email alerts
|

Generation and Novel Distribution of Matrix Metalloproteinase-derived Aggrecan Fragments in Porcine Cartilage Explants

Abstract: We have studied aggrecan catabolism mediated by matrix metalloproteinases (MMPs) in a porcine cartilage culture system. Using antibodies specific for DIPEN 341 Aggrecan is the major proteoglycan present in articular cartilage, and it is the molecule that endows cartilage with its intrinsic capacity to bear load and resist compression. This weight-bearing capacity is dependent on the structure and organization of collagen and aggrecan within the extracellular matrix. Normal turnover of aggrecan is a conservat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
59
0
1

Year Published

2001
2001
2006
2006

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(66 citation statements)
references
References 52 publications
(58 reference statements)
6
59
0
1
Order By: Relevance
“…The medium was concentrated 9-fold on Millipore 10-kDa cutoff centrifugal filter units and used as a source of aggrecanase activity, as described previously (13). G1-G2 (1-3 g) was treated with or without glycosidases and then digested with 1 l of aggrecanase-containing medium at 37°C for the times given in buffer containing 50 mM Tris, pH 7.5, 0.1 M NaCl, and 10 mM CaCl 2 .…”
Section: Expression Of [ 35 S]methionine-labeled G1-g2 In Cellmentioning
confidence: 99%
See 1 more Smart Citation
“…The medium was concentrated 9-fold on Millipore 10-kDa cutoff centrifugal filter units and used as a source of aggrecanase activity, as described previously (13). G1-G2 (1-3 g) was treated with or without glycosidases and then digested with 1 l of aggrecanase-containing medium at 37°C for the times given in buffer containing 50 mM Tris, pH 7.5, 0.1 M NaCl, and 10 mM CaCl 2 .…”
Section: Expression Of [ 35 S]methionine-labeled G1-g2 In Cellmentioning
confidence: 99%
“…However, matrix metalloproteinase cleavage at N 341 2 342 F correlates with late-stage cartilage damage in mouse models of arthritis (10 -12), and it may also be involved in the baseline turnover of aggrecan in vitro (13) and in vivo (14). The products of in vivo proteolysis at both the matrix metalloproteinase and the aggrecanase sites have been found in humans (4,15,17,18) and in mice with experimental arthritis (11, 19 -21).…”
mentioning
confidence: 99%
“…However, 2 studies have shed light on this aspect of aggrecan turnover. Fosang et al (9) demonstrated, using confocal microscopy, that the G1 domain derived from aggrecanase-mediated cleavage of aggrecan (containing a new C-terminal neoepitope termed ITEGE) was localized intracellularly, inside chondrocytes present within sections of intact porcine articular cartilage. After their study, we demonstrated that a commercially purified and biotinylated aggrecan G1 domain-link protein complex (isolated following trypsin digest of aggrecan) could be co-internalized with HA via a CD44-mediated endocytosis event (18).…”
mentioning
confidence: 99%
“…G1 fragments generated by ADAMTS-4 or ADAMTS-5 exhibit a unique carboxy-terminal sequence, ITEGE, recognized by an anti-ITEGE neoepitope antibody (9,19). Cleavage of aggrecan by MMPs, such as MMP-13, yields a G1 with a different carboxy-terminal sequence, DIPEN, that is recognized by an anti-DIPEN neoepitope antibody (9,19).…”
mentioning
confidence: 99%
“…Finally, it has recently been reported that a proportion of aggrecanase-generated G1 domains can be cointernalized with HA by chondrocytes via a CD44-dependent mechanism (58,59), indicating that loss of G1-NITEGE 373 (as well as HA) from the cartilage matrix may occur through a variety of mechanisms. Nevertheless, levels of G1-NITEGE 373 in human synovial fluid have been shown to increase during aging, following acute joint injury, and with progression of OA (13), suggesting that aggrecanase-actuated loss of HA and hyaladherins may be part of a physiologic process that occurs in vivo.…”
mentioning
confidence: 99%